Opportunity to change the future or “institutional trap” - E. V. Rozhkov (Вестник университета)
The author of the article considers research on the current implementation of digital processes in Russia, as well as the consequences of these processes, taking into account the theory of “institutional traps”, including falling into the “digital trap”. The purpose of the article is to identify the weak side of digitalisation of the economy. Scientific works devoted to the problems of identifying organizational and theoretical models of digitalisation form the methodological basis of the study. In the results of the study, the author concludes that the “digital trap” is a feature of “digits” and “digital technologies” that leads to universal control over a person, society and the state. Pervasive control 24/7 using artificial intelligence can lead to helplessness of people who will be doomed to obey the instructions “from above”. The author’s economic assessment of the possibility of changing our being with the help of digital technologies leads to an “institutional trap” and, as a result, to a “digital trap”. Judging by the distribution of money in the budget of the Russian Federation, every year more and more funds are allocated for the promotion of digital projects. Such a rapid integration of digital technologies may indicate, on the one hand, the desire to develop the economy and society, and on the other hand, the need to control each person, while speaking about the security of the state and its values.